Congruence Between Individual Needs, Organizational Climate, Job Satisfaction and Performance1 - Downey, H. Kirk; Hellriegel, Don; Slocum, John W. (Academy of Management Journal, 1975)
The article discusses the proposition that organizational climate interacts with individual personality in influencing job satisfaction and performance. Researches who have analyzed the relative amount of variance accounted for by main effects versus interactive effects are listed. Certain researchers emphasize the importance of maintaining congruence between the individual's needs and those of the organization. Congruence is concerned with the individual-organization fit. Individuals congruent with their work environment may perform at a higher rate and be more satisfied than individuals experiencing a lack of fit. It must be assumed that individuals vary in their sensitivity to different organizational climates as well as in behavior.